Electrolyte imbalance in type 2 diabetes: a case study from the West region of Cameroon - Sayouba, Jean Pierre D.; Asanghanwa, Milca; Njouendou, Abel J.; Kamga, Henri L.; Assob, Jules C. N. (International Journal of Research in Medical Sciences, 2020)
Background: Diabetes mellitus remains a global public health challenge despite advances in medicine, with Cameroon harboring about half a million patients. Electrolyte imbalance has been reported to contribute to the complications observed in diabetes. The aim of this study was to investigate electrolyte disturbances in type 2 diabetic (T2D) patients under follow up in two health facilities (Dschang District Hospital and Bafoussam Regional Hospital) of the West Region of Cameroon. Methods: The study involved 200 T2D patients and 50 non-diabetic control subjects. A questionnaire was used to acquire demographic, anthropometric, clinical and psychosocial data. Fasting blood samples were collected for the determination of fasting plasma glucose (FPG), glycated haemoglobin, calcium, potassium and sodium levels. The diabetic population was divided into two and three groups according to their glycated hemoglobin and FPG levels respectively. The Student’s t-test was used to compare mean values between patients and controls, while the chi square test was used to assess for differences between categorical variables. The significance level was set at 5%. Results: Almost all diabetic patients were diagnosed of hypernatremia (98%) versus 70% for the control group (p<0.001). There was no record of hyponatremia. Hypercalcemia was observed in 30% of the diabetic patients and hypocalcemia in 48%. The prevalence of hyperkalemia was comparable between patients and controls, while control subjects tended to be more hypokalemic (p=0.038). For all three electrolytes investigated, more than 70% of the imbalances were observed in patients with hyperglycemia when compared to patients having normal FPG or hypoglycemia. Conclusions: Electrolyte imbalance is common in type 2 diabetic patients from the West Region of Cameroon, especially those presenting with hyperglycemia.